COVID-19 Pandemic Preparedness in a UK Tertiary and Quaternary Children's Hospital: Tales of the Unexpected. (30th October 2020) - Alders, Nele; Penner, Justin; Grant, Karlie; Patterson, Charlotte; Hassell, Jane; MacDermott, Nathalie; Pincott, Sian; Bamford, Alasdair; du Pré, Pascale; Johnson, Mae; Moshal, Karyn
Abstract: We describe the adaptive coping strategies required in the management of a heterogeneous group of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pediatric patients. The diverse range of presentations, presenting in distinct phenotypic waves, exemplified the importance of preparedness for the unknown. Lessons learned will be essential in planning for a likely second wave of SARS-CoV-2. Abstract : We describe a heterogeneous group of 57 pediatric patients admitted to a tertiary and quaternary care children's hospital and the preparedness required to adapt to managing such a diverse population. Lessons learned at the beginning of the COVID-19 pandemic are described and how this knowledge can be translated into further preparation for an expected second wave of pediatric severe acute respiratory syndrome coronavirus-2 infections.